STUDI PERBANDINGAN HASIL BELAJAR EKONOMI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GI ( Group Investigation) DAN TIPE PBL (Problem Based Learning) - eri purwanti; Teddy Rusman; Nurdin Nurdin (FKIP Unila, 2013)
Objective of this research is to find out the differences of economy learning results by using group investigation (GI) and problem based learning (PBL) cooperative learning. This was a comparative research with quasi experiment approach.Population in this research was 245 Grade X students in SMA Negeri 1 in Kalirejo.70 samples from two different classrooms were taken using cluster random sampling technique. Data were collected with pretest and posttest. Data were analyzed using t-test formula for two big samples that were mutually uncorrelated.The hypothesis test results showed that: (1) there were differences of economy learning results between using GI and PBL cooperative learning models; (2) the average of economy learning results by using GI cooperative learning model, as much as 79.37 were higher than economy learning results by using PBL, cooperative learning model, as much as 75.17, with mean difference as much as 4.200 and tcount 3.873 ttable 1.667. thus, H0 was refused and H1 was accepted.Keywords : learning result, cooperative learning model, GI, PBL.